Finite Element Analysis of the Excavation Stability of Deep and Large Ventilation Shafts of Zimuyan Tunnel Using the Raise Boring Machine Method in a Karst Area - Guofeng Wang; Fayi Deng; Kaifu Ren; Yougqiao Fang; Haiyan Xu (Buildings)
The excavation of deep and large vertical shafts in karst areas can easily lead to sudden changes in the stress field of the surrounding rock and even cause disasters such as cave collapses. To investigate the influence of karst areas on the stability of deep and large vertical shaft excavation using the raise boring machine (RBM) method, based on the ventilation vertical shaft project of Zimuyan Tunnel, the influence of karst caves on the displacement and stress fields of the surrounding rock during the construction stage of the vertical shaft was analyzed using the finite element simulation method. Furthermore, the influence of the cave dimensions and the distance between the cave and the shaft on the stability of the surrounding rock was evaluated. The results indicate that the karst cave caused an increase in the radial displacement of the surrounding rock, and the radial displacements and stress in the surrounding rock increased linearly with depth. However, the radial displacement of the surrounding rock in the range of 20D to 21D (D is the well diameter) above the bottom of the well, and the radial stress of the surrounding rock in the range of 7D above and below the depth of the cave, are significantly affected by the cave. When the cavern size increased from 0 to 2.0D, the maximum radial displacement of the surrounding rock in each construction stage increased by 10.7, 16.6, 2.3, and 2.2 times, respectively. Moreover, when the distance between the cavern and the well was increased from 0.5D to 2.0D, the maximum radial displacements of the surrounding rock corresponding to each construction stage were reduced by 51.5%, 61.6%, 40.7%, and 18.4%, respectively. These findings can provide valuable references for the design, construction, and monitoring of deep and large vertical shafts in karst areas.